2019
DOI: 10.1371/journal.pone.0214052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood culture epidemiology and efficiency in a large European teaching hospital

Abstract: BackgroundBlood cultures remain the gold standard for detecting bacteremia despite their limitations. The current practice of blood culture collection is still inefficient with low yields. Limited focus has been given to the association between timing of specimen collection at different time points during admission and their yield.MethodsWe carried out a retrospective observational study by analyzing all 3,890 sets of cultures collected from the 1,962 admitted patients over the seven-month period of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 28 publications
3
40
1
Order By: Relevance
“…Due to the use of broad‐spectrum antibiotics and prevalence of fastidious microorganisms, culture often fails to detect the culprit. Typically, the positive rate of blood culture is less than 10% 17 . In this study, culture was positive in 5.71% (4/70) of patients.…”
Section: Discussionmentioning
confidence: 45%
“…Due to the use of broad‐spectrum antibiotics and prevalence of fastidious microorganisms, culture often fails to detect the culprit. Typically, the positive rate of blood culture is less than 10% 17 . In this study, culture was positive in 5.71% (4/70) of patients.…”
Section: Discussionmentioning
confidence: 45%
“…It is interesting to note that all the blood cultures from the rural site ( n = 19) that were ordered showed no growth and 72.22% of the blood cultures ( n = 72) sent from urban site also showed no growth. This could be due to multiple reasons which are well documented in the literature[ 13 ]: low yield of blood culture (including in sepsis), transport and collection issues.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main criticisms for obtaining BCs in the ED is the low diagnostic yield. Hence, strategies to improve the diagnostic yield and studies aimed at improving BC yield, such as the implementation of educational programs based on proper BC collection, are warranted [38]. It has been reported that physicians overestimate the likelihood of bacteraemia for many of their patients [3941].…”
Section: Discussionmentioning
confidence: 99%